Regioselective Oxidative Cross-Coupling Reaction: Synthesis of Imidazo[1,2-a]pyridine Fluorophores - Chu, Xianglong; Niu, Yadi; Wang, Xiaodong; Lin, Yunliang; Li, Fuwei; Ma, Chen (Synthesis, 2021)
A rapid access to a series of N-heteroarene fluorophores has been developed on the basis of the palladium-catalyzed direct oxidative C–H/C–H coupling of imidazo[1,2-a]pyridines with thiophenes/furans. The photophysical properties–structure relationship was systematically investigated. The resulting N-heteroarene fluorophores present color-tunable emissions (λem: 431–507 nm in CH2Cl2) and high fluorescence quantum yields (up to 91% in CH2Cl2).
Keywords: imidazo[1,2-a]pyridines; oxidative C–H/C–H coupling; fluorophores; regioselectivity; palladium